ChemInform Abstract: Methane as Raw Material in Synthetic Chemistry: The Final Frontier. Issue 5 (4th February 2014) - Caballero, Ana; Perez, Pedro J.
Abstract Review: different methodologies to activate methane with transition metal complexes as well as few examples of the catalytic functionalization of methane; 60 refs.